The Heidelberg functional foot model: application to cavovarus and equinovarus feet - Campos, Sarah; Salami, Firooz; Chen, Qiuyue; Putz, Cornelia; Tsitlakidis, Stefanos; Wolf, Sebastian Immanuel (Journal of foot and ankle research, 2025)
Multisegment foot models have become increasingly important in biomechanical research and clinical gait analysis but often face limitations in defining joint positions. Often, they rely on simplified methods, such as using the midpoint between two markers to represent a joint, which lacks functional verification. In contrast, phenomenological angles, such as the medial arch angle, bypass joint center calculations, and offer sensitive, radiologically aligned indicators of foot mechanics. The Heidelberg functional foot model (HFFM) integrates functionally verified joint positions in combination with clinically relevant phenomenological measures, thereby enhancing clinical interpretability in gait analysis. The marker placement of the HFFM is based on the Heidelberg foot measurement method (HFMM). A four-segment model (shank, hindfoot, forefoot, and hallux) is defined. Anatomical coordinate systems are established via regression formulas derived from functional joint parameter determination. Kinematic angles are compared with radiological measures. Additionally, six clinically relevant angles of the HFMM are integrated into the HFFM. The method is applied to cavovarus (CV, 19 feet), equinovarus (EV, 31 feet), and typically developed feet (TD, 88 feet). EV feet show more pronounced hindfoot varus and forefoot adduction than CV and TD feet. Within the parameters adopted from the HFMM, EV feet exhibit increased subtalar inversion and a stronger medial arch than CV. Significant correlations are identified between hindfoot/shank flexion, forefoot/hindfoot flexion and medial arch, and radiological angles. The HFFM is sensitive for analyzing equinvarus and cavovarus deformities without applying static offsets due to the functional approach. It enables calculating kinetics to better understand the biomechanics of foot deformities.
Gesehen am 14.01.2026